2021
DOI: 10.1016/j.medj.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsies for residual disease and recurrence

Abstract: Detection of minimal residual disease in patients with cancer, who are in complete remission with no cancer cells detectable, has the potential to improve recurrence-free survival through treatment selection. Studies analyzing circulating tumor DNA (ctDNA) in patients with solid tumors suggest the potential to accurately predict and detect relapse, enabling treatment strategies that may improve clinical outcomes. Over the past decade, assays for ctDNA detection in plasma samples have steadily increased in sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 137 publications
(180 reference statements)
0
18
0
Order By: Relevance
“…Recent results support this approach in multiple cancer types. 23 , 26 In early-stage NSCLC treated by surgery and/or radiotherapy, several recent studies used high-sensitivity methods to test associations between ctDNA detection and patient outcomes after treatment with curative intent 21 , 39 , 40 (see Supplementary Information, available at https://doi.org/10.1016/j.annonc.2022.02.007 ). Here we applied high-sensitivity personalized assays to study a population with earlier stage disease, of whom 70% underwent surgical treatment, and observed lead times of ∼200 days from ctDNA detection to disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results support this approach in multiple cancer types. 23 , 26 In early-stage NSCLC treated by surgery and/or radiotherapy, several recent studies used high-sensitivity methods to test associations between ctDNA detection and patient outcomes after treatment with curative intent 21 , 39 , 40 (see Supplementary Information, available at https://doi.org/10.1016/j.annonc.2022.02.007 ). Here we applied high-sensitivity personalized assays to study a population with earlier stage disease, of whom 70% underwent surgical treatment, and observed lead times of ∼200 days from ctDNA detection to disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 4 With the development of highly-sensitive patient-specific assays, ctDNA has been used to detect MRD in patients with breast, colorectal, lung cancer and other solid tumours. 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 In NSCLC, Chaudhuri et al. 21 demonstrated that residual ctDNA could be detected in 94% of stage I-III patients treated predominantly (35/40 patients) by radiotherapy or CRT who subsequently recurred.…”
Section: Introductionmentioning
confidence: 99%
“…In the frame of malignant disease monitoring and progression, ctDNA has also been used as a marker for guiding therapy and minimal residual disease (MRD). The latter is used for the detection of residual disease, based on the presence of cancer-derived molecular biomarkers, when the bulk cancer is not detectable by conventional investigations, such as medical imaging, for instance, in melanoma and colorectal carcinoma (CRC) [ 6 , 7 , 8 , 9 , 10 , 11 ]. Unfortunately, ctDNA in the bloodstream has a very short half-life, ranging from 30 min to 2 h, causing problems in several areas, including tracking tumor heterogeneity, precision treatment, and rigid protocol standardization ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ctDNA-based decision of adjuvant treatment did not adversely affect patient outcomes (2-year recurrence-free survival of 93.5% vs. 92.4%) in stage II colon cancer while reducing the number of patients receiving adjuvant chemotherapy (15% vs. 28%) compared to SoC. This trial successfully examined the impact of a ctDNA-based adjuvant treatment decision strategy compared to a standard adjuvant decision in stage II colon cancer, and many ongoing clinical trials are investigating whether adjuvant chemotherapy can be modified based on postoperative ctDNA MRD status in various types of early-stage solid cancers [79][80][81][82][83][84][85] (Table 1). The prospective randomized trials of MRD-guided adjuvant treatment can be roughly divided into those with a superiority design of escalation strategy, where intensified treatment regimens are compared with SoC in patients with positive postoperative MRD, and those with a non-inferiority design of de-escalation strategy, where de-intensified regimens (e.g., shortened treatment duration, or reduced dose or even treatment omission) are compared with SoC in patients with negative postoperative MRD.…”
Section: Minimal Residual Disease Evaluation In the Postoperative Periodmentioning
confidence: 99%
“…In contrast, tumor-informed panels generally have a higher sensitivity by targeting a larger number of mutations. However, these methods are more expensive and take longer to generate results compared to tumor-agnostic panels [83,84], b)…”
Section: Practical Considerations For the Application Of Ctdna In Sol...mentioning
confidence: 99%